Diversity and composition of tree species in University of Benin, Benin City, Nigeria (Agriculture, Food, and Natural Resources Journal, 2025)
This study assessed the diversity and composition of tree species of the University of Benin (UNIBEN) in Benin City, Nigeria. Tree characteristics such as diameter at breast height (Dbh) and height measurement were obtained during the field inventory. A complete inventory was carried out in five different sample plots at the University of Benin. Data collected were analysed using biodiversity indices such as Shannon-Wiener diversity index, important value index, dominance index, species evenness, and results were presented in means, percentages, charts, and tables. A total population of 666 trees distributed among 18 families and 41 species was identified, with Fabaceae (14.63%) and Meliaceae (14.63%) being the most dominant families and Tectona grandis being the most occurring tree species with a relative density of 61.11%. However, the diversity index 1.79 > 1 is an indication of moderate diversity. Also, the tree species dominance index of 0.39 was recorded. Hence, urban forests are rich in tree diversity and can provide diverse ecosystem services to their communities. To manage sustainably, an urban forest inventory should be regularly carried out.
Keywords: Biodiversity; Diversity index; Inventory; Species richness